2006
DOI: 10.1111/j.1478-3231.2006.01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical associations of posttransplant fatty liver disease

Abstract: Posttransplant steatosis is common after liver transplant even in patients transplanted for non-NAFLD-related liver diseases. However, it is mostly benign during our follow-up, with only 13% developing steatohepatitis and none with fibrosis or cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
66
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 17 publications
3
66
1
1
Order By: Relevance
“…(6,7) Genetic factors, such as patatin-like phospholipase domain containing 3 (PNPLA3) gene polymorphism, are associated with increased hepatic fat concentration. (10) Posttransplant NAFLD affects 18%-40% of liver transplantation (LT) recipients (11)(12)(13) and even 39%-70% (14,15) of those transplanted for NAFLD-related cirrhosis. Risk factors of posttransplant NAFLD include pretransplant and posttransplant obesity, (11)(12)(13) alcoholic cirrhosis as an indication for LT, posttransplant DM, hyperlipidemia, hypertension, tacrolimus (FK-506) administration, and pretransplant graft steatosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(6,7) Genetic factors, such as patatin-like phospholipase domain containing 3 (PNPLA3) gene polymorphism, are associated with increased hepatic fat concentration. (10) Posttransplant NAFLD affects 18%-40% of liver transplantation (LT) recipients (11)(12)(13) and even 39%-70% (14,15) of those transplanted for NAFLD-related cirrhosis. Risk factors of posttransplant NAFLD include pretransplant and posttransplant obesity, (11)(12)(13) alcoholic cirrhosis as an indication for LT, posttransplant DM, hyperlipidemia, hypertension, tacrolimus (FK-506) administration, and pretransplant graft steatosis.…”
mentioning
confidence: 99%
“…(10) Posttransplant NAFLD affects 18%-40% of liver transplantation (LT) recipients (11)(12)(13) and even 39%-70% (14,15) of those transplanted for NAFLD-related cirrhosis. Risk factors of posttransplant NAFLD include pretransplant and posttransplant obesity, (11)(12)(13) alcoholic cirrhosis as an indication for LT, posttransplant DM, hyperlipidemia, hypertension, tacrolimus (FK-506) administration, and pretransplant graft steatosis. (11) In a study by Finkenstedt et al, (16) the PNPLA3 genotype of the recipient (but not the donor) was associated with the development of posttransplant steatosis.…”
mentioning
confidence: 99%
“…Th e diff erence was, however, not statistically signifi cant. It is important to note that only half of the patients in this cohort had donor biopsy fi ndings available for comparison ( 6 ). In the present study, the prevalence of allograft steatosis at implantation was 30.2 % among those who developed de novo NAFLD compared with 12.6 % among those who did not ( 8 ).…”
mentioning
confidence: 53%
“…Poordad et al ( 5 ) reported four cases of de novo NAFLD that developed early in the post-transplant setting. In another report, NAFLD developed in 40 % of LT recipients aft er a mean follow-up of 44 months ( 6 ). NASH was seen in 13 % .…”
mentioning
confidence: 90%
See 1 more Smart Citation